2013
DOI: 10.1093/ndt/gft351
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of chronic kidney disease and its relation to socioeconomic conditions in an elderly Polish population: results from the national population-based study PolSenior

Abstract: (i) CKD affects almost one-third of the elderly Polish population. (ii) In Poland elderly subjects with CKD are usually unaware of their kidney disease. (iii) In Polish elderly population, CKD is more frequently present among urban residents, non-smokers, abstainers and less physically active people. (iv) Only in women is higher educational status related to the lower risk of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 26 publications
5
35
1
3
Order By: Relevance
“…38 However, it cannot be explained by the deterioration of kidney function with age. 39 In line with numerous previously published studies, 40,41 including ours, 36 it was demonstrated that visfatin/NAMPT levels are related to insulin resistance. A similar association was also found in the present study with a more specific measurement method; however, this correlation was markedly weaker.…”
Section: Discussionsupporting
confidence: 88%
“…38 However, it cannot be explained by the deterioration of kidney function with age. 39 In line with numerous previously published studies, 40,41 including ours, 36 it was demonstrated that visfatin/NAMPT levels are related to insulin resistance. A similar association was also found in the present study with a more specific measurement method; however, this correlation was markedly weaker.…”
Section: Discussionsupporting
confidence: 88%
“…The majority were cross-sectional studies (n=21) on the association between SES and CKD prevalence. Nineteen studies8 15 17 24 35–38 40–42 44 45 47 49–51 54 57 were of moderate quality, nine14 25 26 43 46 52 53 55 56 high and only one48 low (online supplementary tables 2–4). Fourteen articles16 58–66 examined the relationship between SES and CKD progression, across more than 6 978 082 participants (two articles60 65 did not provide the number of participants).…”
Section: Resultsmentioning
confidence: 99%
“…In US about 30–40% of adults aged ≥70, and approximately 50% of those aged ≥80 have CKD [8, 9]. In Poland the prevalence of CKD in the elderly population has been recently estimated at 29.4% [10]. In the elderly CKD exerts stronger effect on the life expectancy than in younger population [11].…”
Section: Discussionmentioning
confidence: 99%